INTESTINAL OBSTRUCTION IN DOGS – A review of five cases - Kavirajan, S; Shiju, M; kanan, TA (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Puppies while playing or simply because of avidity, ingest a variety of foreign bodies. Ingested foreign bodies, which are not stopped in the mouth or oesophagus, enter into the stomach. Once a foreign body has passed through the pylorus, jejunum and ileum appear to be the most common sites of the small intestine obstruction (Capak, et al., 2001). Dogs and cats have indiscriminate eating habits and often hungrily swallow anything which seems even only vaguely edible. All age groups are susceptible to develop foreign body problems but obviously seen in young, playful dogs less than 2 years of age. Males ingest foreign bodies more often than females. Foreign bodies were mostly ingested by mongrels, followed by Dobermanns, Poodles, Cocker Spaniels and Rottweiler. Most of these ileus cases were found in March and October (Capak, et al., 2001). Obstruction of the intestines is always considered an emergency situation. The present paper discusses the surgical removal of foreign body.